P5-S3.01 Developing a multi-pronged quality improvement (QI) strategy to increase Chlamydia trachomatis (CT) retesting rates: building a framework for success. (10th July 2011) - Howard, H; Barandas, A; Creegan, L; Bauer, H; Chow, J; Park, I; Bolan, G
Abstract : Background: CT reinfection is common and linked with adverse reproductive sequelae. Despite strengthened national recommendations and clinician education efforts in California (CA), retesting rates remain low. Our objective was to use a systematic QI approach (assess, intervene, assure, evaluate) to build an effective, feasible, multi-pronged strategy for increasing CT retesting rates in the CA family planning (FP) setting. Methods: We assessed underlying barriers to retesting using two data sources: (1) clinical encounter data from a CA FP program screening 1 million low-income women for CT annually was analysed to determine clinic return and retesting rates among female CT patients 1–6 months post-treatment; and (2) a survey of FP clinicians was used to identify retesting knowledge, attitudes, and practices. A pilot strategy designed from these findings was refined after iterative sessions with key clinic staff and evaluation of existing protocols and electronic systems at select sites. Results: Claims data analyses revealed that while 60% of female CT patients returned to clinic 1–6 months post-treatment, only half were retested. Missed opportunities for retesting were associated with limited visits such as pregnancy tests and birth control refills. Clinician survey results showed that 79% did not prioritise CT retesting, only 33% utilised active retesting strategies, and 73% attributed low retesting rates to low patient return rates. A 4-pronged strategy was implemented: (1) to promote retesting as a high priority, medical directors were shown clinic data demonstrating high reinfection rates, high patient return rates, and low retesting rates; (2) clinic systems-level interventions were introduced (chart prompts, clinic practice tools, express STD screening visits); (3) all levels of clinic staff were trained to provide comprehensive counselling to CT-positive patients on reinfection, partner treatment, and practical ways to remember to retest; and (4) patient education materials were revised to improve readability and reinforce messaging. A detailed checklist was developed as a quality assurance tool to facilitate implementation of each intervention and ensure that any operational loopholes were closed. A plan for evaluating the strategy through future monitoring of retesting rates was developed. Conclusions: By employing a systematic QI approach we were able to tailor specific interventions to address multiple underlying causes of low CT retesting rates.